2016
DOI: 10.3892/mco.2016.726
|View full text |Cite
|
Sign up to set email alerts
|

Totally implantable venous access port systems and associated complications: A single-institution retrospective analysis of 2,996 breast cancer patients

Abstract: Abstract. Totally implantable venous access port systems (TIVAPS) are widely used in breast cancer patients. However, complications are frequent and may necessitate device replacement or removal, resulting in additional patient stress and treatment delays. The aim of the present study was to investigate possible risk factors for complications. A total of 2,996 consecutive female breast cancer patients, with a median age of 50.2 years (range, 21.2-85.5 years) were enrolled in this observational, single-centre s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 27 publications
9
38
1
3
Order By: Relevance
“…In many retrospective studies, the complication rate varied between 6 and 21% and is consistent with the findings. 2,5,7,[9][10][11][12][13][14][15][16][17][18][19][20] Furthermore, in accordance with recent studies, author observed a decreasing trend for early complications. 21 Rare major complication as described in case series reports, such as air embolism, hemothorax, brachial plexus injury and pericardial tamponade did not occur in the series.…”
Section: Discussionsupporting
confidence: 78%
“…In many retrospective studies, the complication rate varied between 6 and 21% and is consistent with the findings. 2,5,7,[9][10][11][12][13][14][15][16][17][18][19][20] Furthermore, in accordance with recent studies, author observed a decreasing trend for early complications. 21 Rare major complication as described in case series reports, such as air embolism, hemothorax, brachial plexus injury and pericardial tamponade did not occur in the series.…”
Section: Discussionsupporting
confidence: 78%
“…Moureau et al reported for 696.370 port catheter days a complication rate of 0.52/1,000 catheter days, whereas infections were described in 0.30/1,000 catheter days and dysfunctions in 0.21/1,000 catheter days (37). The risk of thrombosis is higher if the port system is inserted through the subclavian vein compared to the internal jugular vein (38,39). Furthermore, the stenosis rate is lower with insertion in the jugular vein due to its large diameter and high blood flow (40).…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving continuous infusion of chemotherapy, a totally implantable venous access port plays a central role in allowing the delivery of chemotherapy in the outpatient setting. The most common complications associated with totally implantable venous access port are hemorrhage, pneumothorax, hemothorax, infection, and venous thrombosis . Metastatic spread at the site of the insertion of a totally implantable venous access port is an extremely rare complication, although there are some case reports in Western literature .…”
Section: Introductionmentioning
confidence: 99%
“…The most common complications associated with totally implantable venous access port are hemorrhage, pneumothorax, hemothorax, infection, and venous thrombosis. 2 Metastatic spread at the site of the insertion of a totally implantable venous access port is an extremely rare complication, although there are some case reports in Western literature. [3][4][5][6] This is the first case report of a patient with squamous cell carcinoma (SCC) of the hypopharynx who developed tumor seeding not only at the site of the totally implantable venous access port insertion but also along the tunnel tract of the catheter itself.…”
Section: Introductionmentioning
confidence: 99%